"Guess who I am": Constructing false identities for fraudulent purposes in the Chinese context. (25th November 2019) - Zhong, Xiyun; Zeng, Yantao
Abstract : Pragmaticists have investigated identity construction in various social practices. Yet, seldom have they paid attention to false identities assumed in interactions like fraudulence. This study, by resorting to Chen's (2018) theory on pragmatic identity, investigates 72 real fraud cases in contemporary China, trying to uncover the discursive practices for their fabricated identities and the underlying motivations for these identities. It is found that (i) fabricated identities like the victim identity, the friend/kin identity, the clerk identity, the official identity, and the identity of resourcefulness are often deployed as resources for fraudulent purposes; (ii) speech acts, person-referencing, discourse contents, codes, and sounds of speech are the common discursive practices con artists resort to in fabricating their identities; and (iii) the construction of the fabricated identities results from the con artists' adaptation to the physical, social, and mental world of their targets. The study broadens the scope of identity construction by focusing on that of fabricated identity.